Physical and mathematical evaluation of fetal cardiotocography using a methodology based on probability and entropy - et. al., Sandra Catalina Correa Herrera, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
the behavior of fetal heart rate in antepartum cardiotocography traces has been evaluated using a methodology based on the theory of probability and entropy, with which it is possible to quantify how much far away is the abnormal fetal heart rate from normal. Objective: to confirm through a blind study the clinical applicability of a mathematical diagnosis based on probability and the entropy S/k proportion designed to evaluate the cardiotocographic tracing. Methodology: 90 cardiotocographic tracings were taken with a duration of 20 minutes. Then, the frequency of occurrence of the maximum and minimum values of the fetal heart rate was calculated in 10-second intervals. Subsequently, the probability and the S/k proportion of each trace were evaluated. Finally, a mathematical diagnosis was obtained to distinguish normal from abnormal fetal cardiac dynamics. Results: the values of the S/k proportion for the reactive traces varied between -1.9415 to -1.7170 and between -2.3152 and -1.2789 for the non-reactive ones, respectively. Sensitivity and specificity values were both 100% for diagnosing normality and disease with a Kappa coefficient of one. Conclusion: the clinical applicability of the diagnostic parameters of the physical-mathematical methodology was confirmed, by differentiating normal from abnormal states in groups of cardiotocography traces in 20 minutes.